The Effect Of Stress Towards Performance Of Employees At The Office Of Energy And Mineral Resources In The Makassar City - ., Nursia; ., Nurlina; Ramli, Anwar (Advances in Social Sciences Research Journal, 2017)
The purpose of this study is to determine the effect of stress on the performance of employees at the Office of Energy and Mineral Resources in Makassar. The method used is descriptive survey and explanatory survey method. The type of investigation in this study is causality. The unit of analysis in this study is all employees at the Office of Energy and Mineral Resources in Makassar. The analytical method uses multiple regression with the help of SPSS program. The results showed that individual stressor variables and organizational stressors together have a significant effect on the performance of employees at the Office of Energy and Mineral Resources in Makassar. Then individual stressor variable as the most dominant factor affect the performance of employees at the Office of Energy and Mineral Resources in Makassar.